The COVID-19 Impact on Livelihoods and Poverty in Sri Lanka : Background Note to Sri Lanka Poverty Assessment - World Bank (World Bank, Washington, DC, 2021)
The Coronavirus (COVID-19) crisis has dealt a significant shock to Sri Lanka’s economy and people. This note examines the expected impact on poverty and inequality amid widespread job and earnings losses. While poverty was relatively low in Sri Lanka prior to the pandemic, pre-existing vulnerabilities were high, partly owing to high levels of informality. Many workers do not have access to employment protection or other job-related social protection benefits, making them vulnerable during times of economic crisis. Livelihoods support programs and various relief measures implemented by the government over the course of the pandemic are expected to have mitigated the labor market shock. Inequality is expected to increase in the short run because of the unequal distribution of the shock. Moreover, reduced social mobility as a consequence of widening disparities in access to education for example could increase inequality in the long term. Policy measures could aim to strike a balance between those that support a resilient recovery and those that aim to include the most vulnerable in the recovery process. Achieving this balance will help reverse the impact of the pandemic and mitigate its consequences for inequality. Shifting toward a more adaptive social protection system would allow much needed support to be scaled up quickly and effectively in times of crisis.